SOCIAL LEARNING THEORY DALAM MATERI TATA CARA SUJUD SAHWI DI SD PASIRLAYUNG 03 KABUPATEN BANDUNG - RF, Firyal Yasmin; Tarsono, Tarsono; Sari, Iis Indah; Sonia, Gina Aria; Guswantoro, Hari; Andriawan, Irwan (Attadib: Journal of Elementary Education, 2023)
This study aims to explore social learning theory (Social Learning Theory) in the subject matter of Islamic education class VI at SD Pasirlayung 03 Bandung Regency. Discussion about the definition of social learning theory in prostration sahwi material. This study used a descriptive qualitative approach which was studied through library research and observation. The results of the study show that social learning theory can facilitate students' understanding of prostration for sahwi. Supported by innovative learning mediaTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//